Isolated Amyloid-β Pathology Is Associated with Preserved Cortical Plasticity in APOE4 Alzheimer's Disease Patients. - Assogna, Martina; Motta, Caterina; Bonní, Sonia; Borghi, Ilaria; Casula, Elias P; Martorana, Alessandro; Koch, Giacomo (J Alzheimers Dis, 2022)
BACKGROUND: Long-term potentiation (LTP) like-cortical plasticity impairment and cholinergic neurotransmission deficits have been widely demonstrated in Alzheimer's disease (AD) patients. OBJECTIVE: In this study we aim to investigate the neurophysiological features underlying cognitive decline in AD patients according to the National Institute on Aging-Alzheimer's Association (NIA-AA) classification and APOE genotype. METHODS: 65 newly diagnosed AD patients were enrolled. APOE genotype and lumbar puncture for the analysis of cerebrospinal fluid biomarkers were performed for diagnostic purposes. Patients were subdivided upon NIA-AA criteria, according to the presence of biomarkers of Aβ amyloid deposition (A) and fibrillar tau (T), in four groups: A+/T-E4 (n = 9), A+/T-E3 (n = 18), A+/T+ E4 (n = 21), and A+/T+ E3 (n = 17). We applied intermittent theta burst stimulation over the primary motor cortex to assess LTP-like cortical plasticity and short latency afferent inhibition (SAI) protocol to investigate central cholinergic activity. Patients were followed over 24 months. Cognitive decline was evaluated considering changes in Mini-Mental State Examination scores respect to the baseline. RESULTS: A+/T-E4 patients showed preserved LTP-like cortical plasticity as compared to A+/T-E3 and to A+/T+ patients independently from genotype (p <  0.001). In addition, A+/T-E4 patients showed a slower cognitive decline with respect to A+/T+ E4 (-0.5±2.12 versus -6.05±4.95; post-hoc p = 0.004) and to A+/T+ E3 patients (-4.12±4.14; post-hoc p = 0.028). No differences were found for SAI protocol (p >  0.05). CONCLUSION: Our results suggest that APOE4 in patients with isolated amyloid pathology could exert positive effects on LTP-like cortical plasticity with a consequent slower cognitive decline.